MEK inhibitors and their potential in the treatment of advanced melanoma: the advantages of combination therapy - Tran KA; Cheng MY; Mitra A; Ogawa H; Shi VY; Olney LP; Kloxin AM; Maverakis E (Dove Medical Press, 2015)
Khiem A Tran,1,* Michelle Y Cheng,1,* Anupam Mitra,1 Hiromi Ogawa,1 Vivian Y Shi,1 Laura P Olney,1 April M Kloxin,2 Emanual Maverakis1 1Department of Dermatology, University of California, Davis, Sacramento, CA, USA; 2Department of Chemical and Biomolecular Engineering, University of Delaware, Newark, DE, USA *These authors contributed equally to this work Abstract: The treatment of melanoma has improved markedly over the last several years with the advent of more targeted therapies. Unfortunately, complex compensation mechanisms, such as those of the mitogen-activated protein kinase (MAPK) pathway, have limited the clinical benefit of these treatments. Recently, a better understanding of melanoma resistance mechanisms has given way to intelligently designed multidrug regimes. Herein, we review the extensive pathways of BRAF inhibitor (vemurafenib and dabrafenib) resistance. We also review the advantages of dual therapy, including the addition of an MEK inhibitor (cobimetinib or trametinib), which has proven to increase progression-free survival when compared to BRAF inhibitor monotherapy. Finally, this review touches on future treatment strategies that are being developed for advanced melanoma, including the possibility of triple therapy with immune checkpoint inhibitors and the work on optimizing sequential therapy. Keywords: cobimetinib, trametinib, vemurafenib, dabrafenib, BRAF inhibitor, MAPK pathway